Bidirectional relationship between anxiety disorder and cancer: a longitudinal population-based cohort study - Sang-Hue Yen; Yi-Hsuan Hsu; Doreen Phiri; Chia-Chun Kuo; Hui-Fen Fang; Min-Huey Chung (BMC Cancer)
Abstract Background Although research has highlighted the link between anxiety and cancer, studies on the relationship between the two have produced inconsistent findings. Therefore, we investigated this relationship and also examined which types of cancer are more likely to induce anxiety. Methods This retrospective longitudinal cohort study, conducted in Taiwan from 2003 to 2016, looked at the risk of cancer in 23,255 patients with anxiety disorder and the risk of anxiety in 33,334 patients with cancer diagnosed between 2003 and 2005. For both analyses, a comparison cohort was created using 1:4 case-control sampling. Cox proportional hazard regression models were used to analyze factors related to anxiety disorder or cancer. Results Patients with anxiety were more likely to develop cancer (adjusted hazard ratio [AHR] = 1.29; 95% confidence interval [CI]: 1.23–1.35) compared to those in the comparison group. Particularly high risks were observed for thyroid cancer (AHR: 2.13, CI: 1.60–2.82), skin cancer (AHR: 2.10, CI: 1.63–2.71), and prostate cancer (AHR: 1.97, CI: 1.59–2.47). Patients with cancer were more likely to develop anxiety than those without cancer (AHR: 1.63, 95% CI: 1.56–1.71), with particularly high risks observed in those with nose cancer (AHR: 3.12, 95% CI: 2.41–4.03), leukemia (AHR: 2.54, 95% CI: 1.63–3.96), thyroid cancer (AHR: 2.34, 95% CI: 1.84–2.97), and oral cancer (AHR: 2.04, 95% CI: 1.65–2.52). Conclusions Our findings highlight a bidirectional link between cancer and anxiety disorder. Understanding this two-way connection can help healthcare providers develop effective strategies for managing cancer and anxiety disorders.